Anaerobic co-digestion of cattle manure and liquid fraction of digestate (LFD) pretreated corn stover: Pretreatment process optimization and evolution of microbial community structure. (January 2020) - Wei, YuFang; Yuan, HaiRong; Wachemo, Akiber Chufo; Li, XiuJin
Graphical abstract: Highlights: LFD pretreatment achieved 41.78% more biomethane production. LFD pretreatment increased the stability of AcoD process. LFD pretreatment process was optimized. The diversities of both bacterial and archaeal community were improved. Acetate-utilizing methanogenesis was dominant pathway in the AcoD system. Abstract: Liquid fraction of digestate (LFD) was used to pretreat corn stover to enhance the biomethane production of anaerobic co-digestion (AcoD) with cattle manure. The effects of LFD concentration and water content (WC) for pretreatment on co-digestion performance and microbial community structure were investigated in a batch system. Results showed that the cumulative biomethane yield (CBY) for co-digestion was improved by 16.85%–41.78% compared with the control. The highest biomethane yield of 238.25 mL g VS −1 was obtained at 85% WC for pretreatment and a 5 M LFD concentration, and this yield was 41.78% higher than that in the control. The LFD pretreatment enriched the dominant bacterial phyla ( Firmicutes and Bacteroidetes ), but had little influence on the prevalent archaeal genus ( Euryarchaeota ). This study demonstrated that LFD pretreatment can greatly enhance the biomethane yield of co-digestion of corn stover and cattle manure under optimal parameters.